Bionspired Photocatalysts for Green Hydrogrn Production: Toward Scalable Eco-Enengy Solutions - Ardi Azhar Nampira; Lucas Lima; Thiago Rocha (Yayasan Adra Karima Hubbi, 2024)
In the pursuit of sustainable energy solutions, the development of green hydrogen production technologies has garnered significant attention. Photocatalytic water splitting is one of the most promising methods to generate hydrogen using solar energy. This study focuses on bioinspired photocatalysts for green hydrogen production, aiming to enhance the efficiency and scalability of photocatalytic processes. The research explores the principles behind bioinspired photocatalysts, which mimic the natural processes of photosynthesis in plants, and their potential to provide eco-friendly energy solutions. The primary objective of this research is to investigate novel bioinspired photocatalysts for efficient hydrogen production under solar irradiation. A combination of experimental methods, including synthesis, characterization, and performance evaluation of photocatalysts, was used. The study employs various techniques, such as X-ray diffraction, UV-Vis absorption spectroscopy, and electrochemical tests, to assess the photocatalytic performance under simulated sunlight. The results reveal that the bioinspired photocatalysts exhibit significantly enhanced hydrogen production rates compared to traditional catalysts. Notably, the integration of natural materials such as plant-derived components improves the photocatalytic efficiency and stability. In conclusion, bioinspired photocatalysts hold great promise for large-scale green hydrogen production, offering a sustainable and cost-effective alternative to conventional energy solutions. Future research will focus on optimizing these catalysts for industrial applications.